The Whyte Python world tour : a novel [large type] - Kennedy, Travis (Random House Large Print, 2025)
"A raucous satirical thriller narrated by Rikki Thunder - drummer for the world-famous 1980s heavy metal band Whyte Python - who is unwittingly lured into an elaborate government plot to bring down the Eastern Bloc"--